COP9 Signalosome Controls the Degradation of Cytosolic Misfolded Proteins and Protects Against Cardiac Proteotoxicity. Issue 11 (6th November 2015) - Su, Huabo; Li, Jie; Zhang, Hanming; Ma, Wenxia; Wei, Ning; Liu, Jinbao; Wang, Xuejun
Abstract : Rationale: : Impaired degradation of misfolded proteins is associated with a large subset of heart diseases. Misfolded proteins are degraded primarily by the ubiquitin-proteasome system, but the ubiquitin ligases responsible for the degradation remain largely unidentified. The cullin deneddylation activity of the COP9 signalosome (CSN) requires all 8 CSN subunits (CSN1 through CSN8) and regulates cullin-RING ligases, thereby controlling ubiquitination of a large number of proteins; however, neither CSN nor cullin-RING ligases is known to regulate the degradation of cytosolic misfolded proteins. Objective: : We sought to investigate the role of CSN8/CSN in misfolded protein degradation and cardiac proteinopathy. Methods and Results: : Cardiac CSN8 knockout causes mouse premature death; hence, CSN8 hypomorphism (CSN8 hypo ) mice were used. Myocardial neddylated forms of cullins were markedly increased, and myocardial capacity of degrading a surrogate misfolded protein was significantly reduced by CSN8 hypomorphism. When introduced into proteinopathic mice in which a bona fide misfolded protein R120G missense mutation of αβ-crystallin (CryAB R120G ) is overexpressed in the heart, CSN8 hypomorphism aggravated CryAB R120G -induced restrictive cardiomyopathy and shortened the lifespan of CryAB R120G mice, which was associated with augmented accumulation of protein aggregates, increased neddylated proteins, and reduced levels of total ubiquitinated proteins and LC3-II in the heart. In cultured cardiomyocytes, both CSN8 knockdown and cullin-RING ligase inactivation suppressed the ubiquitination and degradation of CryAB R120G but not native CryAB, resulting in accumulation of protein aggregates and exacerbation of CryAB R120G cytotoxicity. Conclusions: : (1) CSN8/CSN promotes the ubiquitination and degradation of misfolded proteins and protects against cardiac proteotoxicity, and (2) cullin-RING ligases participate in degradation of cytosolic misfolded proteins. Abstract : Supplemental Digital Content is available in the text.